SUPPLY CHAIN ANALYSIS FOR INDONESIAN NICKEL - Ijang Suherman; Ridwan Saleh (Puslitbang tekMIRA, 2018)
It is imperative to increase the value-added of mineral product, especially nickel, as mandated in Law Number 4 of 2009. This law forces government and industry to optimize the added value in this country. The importing countries that perform further processing obtain most benefit from this value added. This creates an opportunity to optimize the value-added products in this country. This research aims to map supply chains along with their product flows and their relation to problem identification, to analyze product development in the supply chain, to analyze the performance of the industrial chain and its impacts on the national economy. Thus, efforts to increase the backward and forward linkages of nickel industry through value-added improvement program, as mandated in the law can be run according to plan. The research approaches were undertaken through direct and indirect surveys. From the results, there is an interrelated success between the value-added improvement policy from the Ministry of Energy and Mineral Resources and the downstreaming policy from the Ministry of Industry. This is indicated by a continuous product flow. By 2020, an estimated 71.7 million tons of nickel ore will be absorbed entirely by smelter of processing and refining in the country. Then the products generated by these smelters will be absorbed by approximately 24% by the domestic stainless steel industry. The contribution to the national economy can boost Gross Domestic Product by approximately 0.526%.